Accompagner sans financer : une nouvelle doctrine d’investissement de l’État au capital des ETI - Laure-Anne Parpaleix; Kevin Levillain; Blanche Segrestin (Revue de la Régulation)
The shareholder state phenomenon sparks controversy. In traditional economic discourse, a shareholder state intervenes to solve a market failure such as a lack of equity financing for a specific group of companies (equity gap). But it is simultaneously accused of preventing perfect competition. How far does the state act like a private investor? What are the doctrines and the investment practices of the shareholder state? In this paper, we analyse the relationship between the French state’s investment doctrine and its implementation in the case of Bpifrance and its investments in mid-size companies. We show that the hypothesis of an equity gap is not sufficient to account for these public investments. We propose an alternative hypothesis: companies may struggle to find buyers ready to support a sustainable growth strategy. The paper thus sheds light on the obstacles to the growth of mid-sized companies: these could result less from a lack of private equity and financial resources than from investment logics unsuited to innovation-led growth. This diagnosis suggests new doctrines for public investment (e.g. market shaping instead of market fixing), but also new ways to support more sustainable and responsible forms of corporate growth.